Representando la voz del pueblo: el lenguaje político en la derogación de la ley de lemas (Santa Fe, 2004) (Estudios Sociales, 2023)
Santa Fe’s political field has suffered different transformations, many of them are registered under changes in the electoral system. Those were promoted by political actors in a context of delegitimization of the system. This investigation focused on the transition from the double simultaneous and cumulative voting system (lemas’s law) to the open, simultaneous and obligatory primaries system (PASO’s law). Thus, from the tools of conceptual history, we aim to describe the interpretations and concepts expressed by the Santa Fe deputies, on the electoral regime modification debate.
Keywords: Political language; lemas law; Santa Fe; legislative reform; conceptual history